Methods of conducting information warfare - Slambekova М.А.; Ishanovа А.К.; Toplu, M. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article highlights the main methods of information warfare, which were identified on the basis of content analysis of domestic and foreign media. Reception is a certain order of actions by which information wars are conducted. The rapid pace of technology development in the new century contributes to the emergence of new techniques, but many of the techniques of information warfare were used long before the advent of the Internet and social networks, and in our time taking into account modern realities they have found a field of application. Such techniques as disinformation, religious and ideological propaganda have been used since historical times, fake news and framing have appeared in modern times. The article presents six methods of conducting information wars, which are demonstrated on specific examples. A table was compiled based on the results of the study with the identified methods of conducting information warfare and their interpretations.